Atsiri Oil Potential of Peel of Kaffir Lime, Lime, and Calamansi Orange as Antioxidant and Antibacteria - Astri Indah Lestari (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Orange is a member of the Rutaceae family which is known as one of the horticultural crops that is widely cultivated in the tropical and subtropical regions of southern Asia. Citrus plants such as fruit peels are used as a source of essential oil-producing ingredients that have antioxidant and antimicrobial activity. This study aims to determine the potential of kaffir lime, lime, and calamansi orange peel essential oils as antioxidants and antibacterials. Scoping review uses the PEOS framework and several databases such as the electronic database Atlantis Press, PubMed, ScienceDirect, and the Google Scholar search engine. Search results that meet the criteria are then analyzed using PRISMA Flowchart, Data Extraction, and Theme Mapping. The results of the scoping review study of 74 articles related to titles and abstracts, 8 articles met the inclusion and exclusion criteria. Essential oils from kaffir lime peel (Citrus hystrix), lime (Citrus aurantifolia), and calamansi orange (Citrus microcarpa Bunge.) have antioxidant and antibacterial activities. The higher the concentration of essential oils from the peel of the fruit, the greater the antioxidant and antibacterial activity produced. Fresh orange peel essential oil has the strongest antioxidant and antibacterial activity compared to orange twig and leaf oil.